Results of treatments the middle reaches of the river Irtysh by preparation "vektobak 12as" against the larvae blackflies in 2012. (Experimental biology, 2015)
The article contains the results of three times working up of Irtysh river by bacteriological preparation «VectoBac12AS» against blackflies larva in 2012. The data on species composition and season dynamic of blackflies quantity aregiven.
Keywords: generation; biopreparation; еffectiveness